2021
DOI: 10.1002/wrna.1659
|View full text |Cite
|
Sign up to set email alerts
|

The many facets of miR‐223 in cancer: Oncosuppressor, oncogenic driver, therapeutic target, and biomarker of response

Abstract: Given their intrinsic pleiotropism, microRNAs (miR) play complex biological roles, in both normal and pathological conditions. Often the same miR can act as oncogene or oncosuppressor, depending on the biological process dysregulated in each specific tissue. miR-223 does not represent an exception to this rule and its functions greatly differ in different contexts. miR-223 has been widely studied in the hematopoietic compartment, where it plays a central role in innate immune response, regulating myeloid diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“…In recent years, studies have confirmed that miRNA is involved in many biological activities, especially the cell proliferation and invasion of malignant tumors, and can be used as a therapeutic target for cancer treatment [ 20 ]. The important role of miRNA in the early diagnosis and prognosis of a series of cancers has been confirmed, such as miR-223 [ 21 ], miR-30a-5p [ 22 ], and miR-105 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have confirmed that miRNA is involved in many biological activities, especially the cell proliferation and invasion of malignant tumors, and can be used as a therapeutic target for cancer treatment [ 20 ]. The important role of miRNA in the early diagnosis and prognosis of a series of cancers has been confirmed, such as miR-223 [ 21 ], miR-30a-5p [ 22 ], and miR-105 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, we observed that miR-223 inhibited HNMT expression. A recent review elaborated the complexities of this miRNA: it can act as either an oncomir or oncosuppressor [40]. Unlike miR-223, data concerning the role of miR-3065 in cancer have been relatively limited; however, miR-3065 was recently found to be a potential predictor of disease severity in ovarian cancer, along with its target ADH7 [41].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-223 is an anti-inflammatory microRNA that acts as a tumor suppressor in TNBC. The published literature has demonstrated that miRNA-223 expression is associated with NLRP3 inflammasome inhibition and the inhibition of cell cycle progression [ 99 , 100 ].…”
Section: Non-coding Rnas In Oncologymentioning
confidence: 99%